DETERMINANTS OF MYOCARDIAL INFARCTION OUTCOMES IN A NON-PERCUTANEOUS CORONARY INTERVENTION HOSPITAL IN JAKARTA - Talitha Syifa Laili; Wiwin Winarti (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Global cardiovascular challenges persist, notably in myocardial infarction (MI). Despite studying factors such as age, sex, MI type, and comorbidities impacting survival, knowledge gaps exist, particularly in Indonesia without recent MI data, especially in non-PCI settings. Objectives: This study seeks to bridge the knowledge gap concerning determinants of post-MI survival in hospitals without PCI facilities in Jakarta, Indonesia. Methods: Adopting a retrospective cross-sectional design, 112 medical record patients from an Emergency Department of non-PCI hospital in Jakarta were selected via purposive sampling. A structured checklist was utilized to assess 16 variables and the primary endpoint was post-treatment status. The study employed Chi-square, Fisher's exact, and Likelihood ratio tests to analyze the relationship between demographics, risk Factors, and MI treatment access and the post-treatment status. Results: Results highlighted that of 112 myocardial infarction (MI) patients, males constituted 70.5%, with Non-ST Elevation Myocardial Infarction as the predominant subtype (57.1%). Most participants (86.6%) were ≥45 years old. Prevalence rates included hypertension (56.3%), Diabetes Mellitus (40.2%), Congestive Heart Failure (42.0%), and prior MI (27.7%). Post-MI survival stood at 92.9%, with 7.1% mortality. The results revealed a significant correlation between cardiogenic shock and MI outcomes (p=0.000), indicating a protective advantage (OR: 0.018) for those without cardiogenic shock against MI-related mortality. Conclusion: While cardiogenic shock has been reaffirmed as the sole predictor of post-myocardial infarction mortality in our study, it's crucial to heighten awareness of other MI determinants, including age, gender disparities, smoking status, and the dynamics of therapeutic measures. This underlines the pressing need for early identification and evidence-based management strategies.